Sex Pheromone Receptors of Lepidopteran Insects - Chan Yang; Jie Cheng; Jingyu Lin; Yuan Zheng; Xiao Yu; Jinpeng Sun; Jinpeng Sun (Frontiers in Ecology and Evolution, 2022)
The sex pheromone receptors (SPRs) of Lepidopteran insects play important roles in chemical communication. In the sex pheromone detection processes, sex pheromone molecule (SPM), SPR, co-receptor (Orco), pheromone binding protein (PBP), sensory neuron membrane protein (SNMP), and pheromone degradation enzyme (PDE) play individual and cooperative roles. Commonly known as butterfly and moth, the Lepidopteran insects are widely distributed throughout the world, most of which are pests. Comprehensive knowledge of the SPRs of Lepidopteran insects would help the development of sex lure technology and the sex communication pathway research. In this review, we summarized SPR/Orco information from 10 families of Lepidopteran insects from corresponding studies. According to the research progress in the literature, we speculated the evolution of SPRs/Orcos and phylogenetically analyzed the Lepidopteran SPRs and Orcos with the neighbor-joining tree and further concluded the relationship between the cluster of SPRs and their ligands; we analyzed the predicted structural features of SPRs and gave our prediction results of SPRs and Orcos with Consensus Constrained TOPology Prediction (CCTOP) and SwissModel; we summarized the functional characterization of Lepidopteran SPRs and SPR-ligand interaction and then described the progress in the sex pheromone signaling pathways and metabotropic ion channel. Further studies are needed to work out the cryo-electron microscopy (EM) structure of SPR and the SPR-ligand docking pattern in a biophysical perspective, which will directly facilitate the understanding of sex pheromone signal transduction pathways and provide guidance in the sex lure technology in field pest control.